2020
DOI: 10.1039/d0ra07569h
|View full text |Cite
|
Sign up to set email alerts
|

Green and facile sol–gel synthesis of the mesoporous SiO2–TiO2catalyst by four different activation modes

Abstract: The most environmentally friendly protocol for obtaining mesoporous SiO2–TiO2 catalysts has been sought.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 45 publications
(31 reference statements)
0
5
0
Order By: Relevance
“…The peak in the region of 445 cm -1 is related to stretching vibrations of Fe 3+ -O 2with tetrahedral spatial arrangement which overlaps with the peaks related to zeolite. Peaks in the region of 738 and 810 cm -1 are assigned to the Ce-O-Si and Fe-O-Si bands [29][30][31]. The broadening of the peak related to zeolite indicates the placement of cerium ions in the structure of the zeolite network.…”
Section: Investigating Photodegradation Of 4-nitrophenol Using Cfdazy...mentioning
confidence: 99%
“…The peak in the region of 445 cm -1 is related to stretching vibrations of Fe 3+ -O 2with tetrahedral spatial arrangement which overlaps with the peaks related to zeolite. Peaks in the region of 738 and 810 cm -1 are assigned to the Ce-O-Si and Fe-O-Si bands [29][30][31]. The broadening of the peak related to zeolite indicates the placement of cerium ions in the structure of the zeolite network.…”
Section: Investigating Photodegradation Of 4-nitrophenol Using Cfdazy...mentioning
confidence: 99%
“…The observed variance may suggest differences in the amounts of surface hydration or the configurations of hydrogen bonding inside the synthesised silica. [46][47][48][49] The spectral peak observed at a wavenumber of 1630.10 cm À 1 is frequently attributed to bending vibrations, commonly associated with adsorbed water molecules. [47] The observed presence may indicate differences in the moisture content on the surface of the synthesised silica compared to the silica by Sigma Aldrich.…”
Section: Ftir Analysismentioning
confidence: 99%
“…This implies that there may be variations in the hydroxyl content or arrangement of surface hydroxyl groups between the two silica samples. The observed variance may suggest differences in the amounts of surface hydration or the configurations of hydrogen bonding inside the synthesised silica [46–49] …”
Section: Ftir Analysismentioning
confidence: 99%
“…S6 †). 57 The chemical shift, entire individual line width at half height, and the percentage of Q n obtained from 29 Si MAS NMR are summarized in Table S2. † It was found that the proportions of Q 2 , Q 3 , and Q 4 in Ti 0.5 Si 0.5 O 2 were 2.7%, 53.4%, and 43.9%, respectively, demonstrating that Q 2 and Q 3 accounted for a significant amount of the Si-O-Ti bonds.…”
Section: Characterizationmentioning
confidence: 99%